Concrete and sustainability - Jahren, Per; Sui, Tongbo (CRC Press, Taylor and Francis Group Chemical Industry Press, 2014)
"Concrete is the second most common commodity in the world, after water, and by far the most common building material. The industry has a great deal of responsibility for sustainable development. This book demonstrates the importance of sustainable thinking, examines the range of challenges facing the concrete engineer, and outlines how they can be addressed. It balances account resource availability, technical